(untitled) (Ágora de Heterodoxias, 2018)
The article analyzes the construction and representation of spaces and subjects in the modern Caribbean tourism imaginary and its relationship with the production and circulation of images, civilizing processes, and the development of capitalism, which date from the beginnings of the European presence in the basin, during the 16th century. The analysis is built around William Shakespeare’s play The Tempest, mostly on the metaphor of the relationship between Prospero and the island, and with its native inhabitants in particular with Calibanon. By making use of the Shakespearean work of the colonial historical processes of the Caribbean in the first European descriptions of the area protrayed in the dairies of Columbus, the development of the slave plantation, and the establishment of modern tourism, this article proposes that the vast majority of colonial dynamics still persist in the perception and use of the Caribbean as a tourist destination.